Information and communication technologies as a tool of strategy for ensuring the higher education adaptability to the digital economy challenges - Kholiavko, Nataliia; Popelo, Olha; Bazhenkov, Ievgen; Shaposhnykova, Iryna; Sheremet, Oleg (My University, 2021)
The intensification of the processes of the digital economy development is leading to the transformation of the higher education system. Universities are forced to digitalize their owneducational, research, international, marketing, financial and economic activities in order to maintain a competitive position in the global market of educational services. The purpose of the article is to study the role of information and communication technologies in the development of the higher education system and to ensure its adaptability to modern challenges of digital economy. To achieve this goal, methods of content analysis, logical generalization, systematization and a structural-functional method are used. In the article, the authors substantiate the urgency of forming a holistic strategy to ensure the adaptability of higher education to the challenges of digital economy. In the structure of this strategy, the information-technological block is singled out and described. The authors specified a set of positive synergetic effects from the introduction of modern information and communication technologiesin the activities of universities. The main information threats to the digitalization of higher education related to the protection of personal data and university systems fromcyberattacks and fraudulent schemes are identified. In conclusion, the authors detail the measures for the strategy implementation to ensure the adaptability of higher education to digital economy. Інтенсифікація процесів розвитку цифрової економіки призводить до трансформації системи вищої освіти. Університети змушені цифровізувати власну освітню, дослідницьку, міжнародну, маркетингову, фінансово-економічну діяльність, щоб зберегти конкурентні позиції на світовому ринку освітніх послуг. Метою статті є дослідження ролі інформаційно-комунікаційних технологій у розвитку системи вищої освіти та забезпечення її адаптивності до сучасних викликів цифрової економіки. Для досягнення цієї мети використовуються методи контент-аналізу, логічного узагальнення, систематизації та структурно-функціональний метод. У статті автори обґрунтовують актуальність формування цілісної стратегії забезпечення адаптивності вищої освіти до викликів цифрової економіки. У структурі цієї стратегії виділено та описано інформаційно-технологічний блок. Автори визначили сукупність позитивних синергетичних ефектів від впровадження сучасних інформаційно-комунікаційних технологій у діяльність університетів. Визначено основні інформаційні загрози цифровізації вищої освіти, пов'язані із захистом персональних даних та університетських систем від кібератак та шахрайських схем. На завершення автори детально описують заходи щодо реалізації стратегії забезпечення адаптивності вищої освіти до цифрової економіки.
Keywords: кафедра економіки праці та менеджменту; information and communication technologies; digitalization; blockchain; вища освіта; цифрова економіка; цифрова економіка; інформаційно-комунікаційні технології; цифровізація; блокчейн; блокчейн